2017
DOI: 10.1002/ptr.5873
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oral Bioavailability of Diltiazem by the Influence of Gallic Acid and Ellagic Acid in Male Wistar Rats: Involvement of CYP3A and P‐gp Inhibition

Abstract: The oral bioavailability of diltiazem is very low due to rapid first pass metabolism in liver and intestine. The purpose of the study was to investigate the effect of gallic acid and ellagic acid on intestinal transport and oral bioavailability of diltiazem in rats. The intestinal transport and permeability of diltiazem was evaluated by in vitro non-everted sac method and in situ single pass intestinal perfusion study. The oral pharmacokinetics was evaluated by conducting oral bioavailability study. The intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…It is mostly accepted that bioavailability can vary among different phenolic acids, and the dietary abundance of a specific compound does not necessarily translate to best bioavailability profile. Although available experimental studies in animals and humans have demonstrated that gallic acid can be absorbed in the body [85,87,88,89], its effectiveness can be hindered due to rapid metabolism and elimination [85,86]. Furthermore, like most natural products, additional studies specific to determining food species with properties that elevate gallic acid bioavailability, and knowing how much of certain foods one need to consume to have the beneficial dosage of this phenolic acid in plasma are required.…”
Section: A Brief Overview Of the Classification Occurrence And Bmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mostly accepted that bioavailability can vary among different phenolic acids, and the dietary abundance of a specific compound does not necessarily translate to best bioavailability profile. Although available experimental studies in animals and humans have demonstrated that gallic acid can be absorbed in the body [85,87,88,89], its effectiveness can be hindered due to rapid metabolism and elimination [85,86]. Furthermore, like most natural products, additional studies specific to determining food species with properties that elevate gallic acid bioavailability, and knowing how much of certain foods one need to consume to have the beneficial dosage of this phenolic acid in plasma are required.…”
Section: A Brief Overview Of the Classification Occurrence And Bmentioning
confidence: 99%
“…Similarly, other researchers showed that using other systems such as phospholipid complexation or microencapsulation can enhance the therapeutic efficacy of gallic acid through increasing absorption and bioavailability in serum [92]. Recently, it has been shown that gallic acid significantly enhanced the bioavailability of diltiazem, a calcium channel blocker widely used to treat hypertension, leading to the inhibition of both cytochrome P450 isozyme (CYP3A)-mediated metabolism and P-glycoprotein-mediated efflux in the intestine and/or liver [87]. This result is of interest since the process of absorption, distribution, metabolism, and excretion of different agents can be affected by co-treatment with other drugs, as well as various physiological and pathological changes.…”
Section: A Brief Overview Of the Classification Occurrence And Bmentioning
confidence: 99%
“…3a) [40]. Recently, it has been confirmed that ellagic acid can significantly inhibit CYP3A and P-glycoprotein (P-gp)-mediated efflux in the intestine [41], thus, increase warfarin plasma concentration and its pharmacological effect.…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid is also reported to inhibit both the enzymes at IC 50 values of 87.24 ± 1.11 μg/ml and 92.03 ± 0.38 μg/ml, respectively (Ponnusankar, Pandit, Babu, Bandyopadhyay, & Mukherjee, ). Gallic acid (50 mg/kg) and ellagic acid (50 mg/kg) are reported to enhance oral bioavailability of Diltiazem (15 mg/kg) in male Wistar rats by increasing the C max , AUC 0 ‐t , and AUC 0‐∞ and decreasing CL by almost two fold each ( p < .05) (Athukuri & Neerati, ). Therefore, we propose that further in vivo studies involving humans or animals to evaluate the effect of concomitant administration of Terminalia bellerica with conventional cardiovascular drugs metabolized by CYP3A4 and CYP2D6 needs to be carried out to identify potential HDI.…”
Section: Herbs Administered In Cvd and Their Reported Hdi With Cardiomentioning
confidence: 99%